Pengaruh Kepemimpinan Diri, Lingkungan Kerja Terhadap Pengembangan Karir Penerbang Di Indonesia Dengan Motivasi Sebagai Variabel Intervening - Allendia Traviana; Agus Fauzi; Nurhasanah (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2021)
Pilot’s leadership is one of the most important factors that profoundly influences flight safety. In addition, the career development requires leadership quality. Strong leadership begins first on the inside, yet it requires environmental support. The purpose of this research is to analyze the relationship between selfleadership, work environment, motivation and career development of Indonesian Pilots. Data was collected through structured survey using questionnaire with Category Scale. Probability sampling technique was used to collect data from 250 Captain Pilots in 10 different airlines in Indonesia. The tool of analysis which is used is partial least square 3.2.9 with structural equation model analysis (SEM). Partial measurement is analyzed by examine significant value. Simultaneous measurement is analyzed using Ftest calculation. And mediation is analyzed using t-test, Sobel-test and VAF-test. The study identified that: (1) self-leadership has a positive correlation to work environment (2) self-leadership has positive and significant effect on the career development (3) work environment has positive and significant effect on the career development (4) self-leadership and work environment have positive and significant effect on the career development simultaneously (5) self-leadership has positive and significant effect on the motivation (6) work environment has positive and significant effect on the motivation (7) self-leadership and work environment have positive and significant effect on the motivation simultaneously (8) motivation has positive and significant effect on the career development. This research, inclusively, have shown the structural equation model SEM PLS is adequate and the overall data processing is proven.